TEACHING FUTURE MUSICIANS PROFESSIONALLY DIRECTED LEXICAL COMPETENCE - Nataliya Vyspinska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article is devoted to the theoretical basis of the professionally directed English language lexical competence formation methods in the process of listening of higher education students by the example of "Music education" specialty. The psycholinguistic peculiarities of teaching lexical and professionally directed lexical competence to the students with musical abilities have been analysed. It reveals the essence of the process of listening and refines the notion of lexical and professionally directed lexical competence. This study provides evidence that music and language have much in common and reveals neurophysiological explanations for musician's higher learning abilities, particularly in vocabulary acquisition. Recommendations for the development of the new methods of lexical and professionally directed lexical competence training have been given.